E-learning: a Modality of Medical Education in the Period of Crisis - Baral, Gehanath; Baral, Reetu Sharma (Journal of Nepal Health Research Council, 2021)
Delivery of medical education is challenged during the crisis like in pandemic. The purpose of this review is to explore the possible modality of medical education in pandemic condition. The modality depends on the availability of modality based resources, set curriculum and acceptance of modality. Blended learning and e-learning appear as the options of teaching-learning in crisis situation. Medical schools may adopt blended learning and e-learning modalities through curriculum that requires capacity building and availability of e-learning tools. Rescheduling the practical and clinical part in both training and evaluation are the immediate actions. Thus the existing method should be optimized by revision, replacement or postponement. Keywords: Crisis; curriculum; e-learning; medical education; pandemic